The Technology Readiness and Perceived Usefulness Mediate Digital Competencies and Artificial Intelligence Technologies - Ardiyanti, Alfi; Susilowati, Endah (LP3M Universitas Putra Bangsa, 2024)
The development of technology is getting more sophisticated along with the increasing number of fields that adopt technology, such as artificial intelligence. Universities are now adding AI curriculum in accounting as a provision before entering the workforce. There are factors that can influence users in accepting technology so this study aims to examine the influence of variables on AI acceptance. This research is a quantitative study with a primary data collection method through a questionnaire distributed to 98 respondents with a population of 4,074 students with research objects at 4 state universities in Surabaya. The results of the research conducted are that digital competence affects technology adoption of AI, technology readiness and perceived usefulness, technology readiness affects technology adoption of AI and perceived usefulness affects technology adoption of AI. Technology readiness and perceived usefulness cannot mediate the effect of digital competence and technology adoption of AI.